2014
DOI: 10.1587/transele.e97.c.976
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Sector Antenna with the Same Beamwidth Employing Multiple Woodpile Metamaterial Reflectors

Abstract: SUMMARY This paper proposes a sector base station antenna for mobile wireless communication systems employing multiple woodpile metamaterial reflectors and a multiband radiator that establishes the same beamwidth in the horizontal plane for more than two frequency bands. Electromagnetic Band Gap (EBG) characteristics of each metamaterial reflector can be controlled through structural parameters of the woodpile reflector, e.g., the rod width and rod spacing. As an example of the proposed antenna, a design for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The metamaterial antenna comprises a dipole radiator and a woodpile reflector. The woodpile reflector consists of the woodpile metamaterial and has EBG characteristics [13], [17]. The woodpile reflectors can reflect/transmit electromagnetic waves according to the frequency characteristics which works as a band-stop or bandpass filter.…”
Section: A Directional Antenna Employing Woodpile Reflectormentioning
confidence: 99%
See 2 more Smart Citations
“…The metamaterial antenna comprises a dipole radiator and a woodpile reflector. The woodpile reflector consists of the woodpile metamaterial and has EBG characteristics [13], [17]. The woodpile reflectors can reflect/transmit electromagnetic waves according to the frequency characteristics which works as a band-stop or bandpass filter.…”
Section: A Directional Antenna Employing Woodpile Reflectormentioning
confidence: 99%
“…Fig. 3 shows the proposed lightweight woodpile meta- The thickness of the woodpile reflector should be thin because the multiband antenna discussed in [12], [13] places multiple reflectors. Then the thickness of the woodpile reflector is set to one period.…”
Section: B Lightweight Woodpile Reflectormentioning
confidence: 99%
See 1 more Smart Citation
“…FSS (frequency selective surface) and EBG (electromagnetic band gap) have useful characteristics for various antenna patterns. Reference [4] shows that by using multiple woodpile metamaterial reflectors and a radiator, it is possible to establish the same beamwidth for a triplefrequency band. Further, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that using frequency selective reflector (FSR) as the reflector of the RBD antenna is effective to configure the multiband mobile base station antennas [5,6,7]. In the base station antennas, the beamwidth in the horizontal plane is important to cover sector service area and to suppress the interference toward the adjacent sectors [1,2].…”
Section: Introductionmentioning
confidence: 99%